2018
DOI: 10.3390/nu10111674
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Food Variety in Chinese Children Aged 3–17 Years: Are They Negatively Associated with Dietary Micronutrient Inadequacy?

Abstract: Micronutrient inadequacy remains a nutritional problem in Chinese children. However, the associations between dietary diversity and inadequate micronutrient intake have not been extensively studied. A total of 2012 children aged 3–17 years from the China Health and Nutrition Survey were included for analysis. Dietary diversity score (DDS) and food variety scores (FVS) were assessed based on three 24-h recall periods. The nutrient adequacy ratio (NAR) was used to determine the micronutrient adequacy of the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 26 publications
7
60
7
Order By: Relevance
“…While dietary diversity was not quantitatively measured using a score in the current study, a similar pattern emerged, wherein consumption of a less variety of foods was associated with increased nutrient inadequacies [4]. A recent study in Chinese children and adolescents found that children who consumed a greater variety of foods presented lower nutrient inadequacies [24]. This was comparable to the findings in younger Filipino children [5].…”
Section: Lack Of Dietary Diversity As the Root Of Inadequate Nutrientsupporting
confidence: 69%
“…While dietary diversity was not quantitatively measured using a score in the current study, a similar pattern emerged, wherein consumption of a less variety of foods was associated with increased nutrient inadequacies [4]. A recent study in Chinese children and adolescents found that children who consumed a greater variety of foods presented lower nutrient inadequacies [24]. This was comparable to the findings in younger Filipino children [5].…”
Section: Lack Of Dietary Diversity As the Root Of Inadequate Nutrientsupporting
confidence: 69%
“…At present, many studies are based on the analysis of specific groups or regions. For example, Zang [32]. However, it is also very important to understand whether the overall dietary structure of Chinese people can guarantee human health from a macro perspective, which is an important basis for policymakers to refer to.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many studies are based on the analysis of specific groups or regions. For example, Zang et al used DBI scores to evaluate dietary quality across seasons in Shanghai, China [ 30 ]; Wang et al evaluated Chinese dietary habits by focusing on the obesity rate [ 31 ]; Meng et al discussed the nutritional problem among Chinese children caused by micronutrient inadequacy [ 32 ]. However, it is also very important to understand whether the overall dietary structure of Chinese people can guarantee human health from a macro perspective, which is an important basis for policymakers to refer to.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies explored the dietary diversity status of Chinese children and examined its correlated factors, such as household sociodemographic characteristics, children’s eating habits, and micronutrient inadequacy [23,24]. To the best of our knowledge, however, none of these studies were undertaken in the poor, rural areas of China, where children suffer more, if not the most, from malnutrition.…”
Section: Introductionmentioning
confidence: 99%